2020
DOI: 10.1038/s41467-020-18643-x
|View full text |Cite
|
Sign up to set email alerts
|

Fgf and Wnt signaling interaction in the mesenchymal niche regulates the murine hair cycle clock

Abstract: Tissue growth in the adult is an orchestrated process that often requires biological clocks to time stem cell and progenitor activity. Here, we employed the hair follicle, which cycles between growth and regression in a timely-restricted mode, to show that some components of the hair cycle clock reside within the mesenchymal niche of the hair follicle, the dermal papilla (DP), and both Fgf and Wnt signaling pathways interact within the DP to regulate the expression of these components that include Wnt agonists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 48 publications
(88 reference statements)
1
39
0
Order By: Relevance
“…R-spondins are Wnt activators which function through both the canonical and non-canonical Wnt/βcatenin pathways. All four R-spondins are expressed in the mouse anagen DP and injection of Rspo1, Rspo2, and Rspo3 into adult mouse dermis induces rapid telogen to anagen transition and activation of epidermal follicular stem cells (Li et al, 2016;Smith et al, 2016;Hagner et al, 2020;Harshuk-Shabso et al, 2020). Much less is known about the role of R-spondins in hair follicle development.…”
Section: Discussionmentioning
confidence: 99%
“…R-spondins are Wnt activators which function through both the canonical and non-canonical Wnt/βcatenin pathways. All four R-spondins are expressed in the mouse anagen DP and injection of Rspo1, Rspo2, and Rspo3 into adult mouse dermis induces rapid telogen to anagen transition and activation of epidermal follicular stem cells (Li et al, 2016;Smith et al, 2016;Hagner et al, 2020;Harshuk-Shabso et al, 2020). Much less is known about the role of R-spondins in hair follicle development.…”
Section: Discussionmentioning
confidence: 99%
“…We carried out gene set enrichment analysis (GSEA) and pathway analysis of Kyoto Encyclopedia of Genes and Genomes (KEGG) as well as GO to identify signaling pathways involved in the regulation of macrophage function, and we found that NOD-like receptor (NLR) and WNT signaling pathways were enriched in TRMs relative to mono-macrophages (Figure 2I). NLR is responsible for detecting pathogen-associated molecules or host-derived damage signals (Griebel et al, 2014), and the WNT pathway is associated with the epidermis and hair follicle development (Andl et al, 2002;Harshuk-Shabso et al, 2020). Immunofluorescence staining showed that CD163 + TRMs and CX3CR1 + mono-macrophages distributed throughout the dermis of the early and middle developmental stages, and more cells emerged in the middle stage.…”
Section: Characterization Of Myeloid Cells In Fetal Skinmentioning
confidence: 99%
“… 9 In zebra fish, Notum regulates motor axon guidance. 10 In mammals, Notum regulates fat metabolism, 11 liver glucose homeostasis, 12 colon stem cell aging, 13 bone strength, 14 , 15 dentin morphogenesis, 16 tracheal development, 17 catagen progression in dermal papilla, 18 and ghrelin hormone deactivation. 19 Notum also plays a key role in adult brain ventricular–subventricular zone neurogenesis.…”
Section: Introductionmentioning
confidence: 99%